ISO 9126 UNTUK PENGUJIAN GAME EDUKASI MEMBUANG SAMPAH BERBASIS ANDROID - Silvia Ratna (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
Games are applications that are familiar to people from all walks of life. Efforts to increase the efficiency of providing applications that contain educational elements require a variety of alternatives and new innovations in programming to be applied as a tool to simplify the learning process. This study aims to create a game design called the game